2009
DOI: 10.1007/s10689-009-9232-1
|View full text |Cite
|
Sign up to set email alerts
|

Men in the women’s world of hereditary breast and ovarian cancer—a systematic review

Abstract: Little is known about men seeking genetic counseling for hereditary breast and ovarian cancer (HBOC). We review the sparse literature on men attending such genetic consultations. Two main themes are identified: the women's influence on the genetic counseling process, and the psychological impact on men. The women in the HBOC families have an influence on the men's decision to request genetic testing, and they take the leading role in communicating genetic information. With respect to psychological impact, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 54 publications
(154 reference statements)
8
47
0
Order By: Relevance
“…Consistent with previous literature, all respondents reported feelings of guilt about transmitting the mutation to future children (19). In a survey of 213 women of reproductive age affected by hereditary breastovarian cancer, 90% were concerned about passing the mutation on to their children (20).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with previous literature, all respondents reported feelings of guilt about transmitting the mutation to future children (19). In a survey of 213 women of reproductive age affected by hereditary breastovarian cancer, 90% were concerned about passing the mutation on to their children (20).…”
supporting
confidence: 79%
“…Respondents expressed concern that men with a BRCA mutation were less concerned with hereditary transmission. Despite this, some studies have shown men do experience similar feelings of guilt about the possibility of passing on a mutation to their children (23) and in difficulty sharing test results with family members (19). …”
mentioning
confidence: 99%
“…Little is known about BRCA1/2-positive males, and the few available studies regarding men in HBOC families have reported low rates of male participation among mutation carriers [8]. Two studies have reported that the motivation for genetic testing among men in HBOC families was fear of cancer or worries about their own health [15, 16], and only one study has focused solely on BRCA1/2 mutation-positive men [10].…”
Section: Discussionmentioning
confidence: 99%
“…Little research attention has been paid to male experiences in HBOC families [8]. The sparse literature available describes men as mainly seeking genetic testing out of an obligation to their children [913], and it is reported that women have a strong influence upon male decision-making regarding genetic testing [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation